SUPPORTIVE COMMUNICATION IN THE PROGRAM FOR HANDLING VIOLENCE AGAINST MUSLIM CHILDREN AT DP3AP2KB BOGOR - Ainun Nafisah; Ellys Lestari Pambayun (Takafu: Journal of Tafsir and Gender Perspective, 2026)
This study aims to explore the implementation of supportive communication in programs addressing violence against Muslim children at DP3AP2KB in Bogor Regency. Using the theoretical foundations of Burleson and MacGeorge as well as Jack Gibb's supportive behaviors, this study analyzes the integration between universal psychological techniques and Islamic spiritual education. The research results show that DP3AP2KB implements the "Islam-Based Supportive Communication (Teo-Psychological)" model, which combines scientific support (medical-psychological) and divine support (spiritual). The implementation is carried out through two main tracks: individual-centered development and the utilization of positive emotions through person-centered messages, such as the use of qashash methods (Prophets' stories) and creative media (drawing/sholawat) to restore the soul (nafs). The six supportive behaviors of Gibb, descriptiveness, problem orientation (5W+1H analysis), spontaneity, empathy, equality, and provisionalism are applied consistently to build victims' trust. The gender factor of officers, who are mostly female, has been proven to increase victims' self-disclosure. This study concludes that supportive communication based on the values of mawaddah wa rahmah and the principle of watawashau bil haqqi wa shabr is effective in alleviating trauma and restoring victims' dignity. Practically, this research recommends strengthening body anatomy literacy and digital parenting to break the chain of child violence in the cyber era.